PROJECT PROPOSAL Arctic Adaptation Exchange: Facilitating Adaptation to Climate Change. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2013)
"Objective of Project: To develop an on-line information portal that: i) provides appropriate access to data, knowledge and decision-support tools needed by governments, industry, Arctic indigenous peoples and other residents to manage climate change risks; ii) enables the sharing of exiting tools and practical adaptation experiences including local and traditional knowledge across the Arctic, and; iii) facilitates the development of new practices and tools that support adaptation decision-making (e.g. arctic wide adaptive capacity indices). Through these functions the portal will enhance adaptive capacity and foster innovation, learning-by-doing, and the development of best practices. The portal will be designed to ensure that it is practical, scalable to resource availability, user-driven (to ensure that it can be easily maintained), and flexible to adjust to shifting priorities." /./